AGRIBUSINESS AND SUSRAINABILITY: legal and environmental interfaces - Oliveira, Vinicius Rogério de; Cavichioli, Fabio Alexandre (Revista Interface Tecnológica, 2025)
Agribusiness holds undeniable importance for the country’s economy, being one of the main sectors of national development. However, its expansion has been accompanied by various social and environmental challenges, highlighting the need to harmonize economic growth with environmental responsibility. Thus, sustainability becomes the central point of discussion, especially regarding compliance with environmental regulations and more conscious agricultural practices. In this context, the purpose of this study is to examine the interactions between the agricultural sector and sustainability in Brazil, focusing on the legal and environmental issues associated with agricultural and livestock activities in the country. The analysis is based on the assumption that agribusiness is fundamental to the national economy; however, it faces significant obstacles concerning environmental preservation and compliance with current laws. An analysis of the current legislation regulating agricultural activity is carried out through a review of relevant bibliographic and documentary sources, such as the Forest Code and the National Environmental Policy. The results indicate the feasibility and importance of implementing sustainable practices in the agricultural sector; however, this implementation requires effective public policies, strict oversight, and greater awareness among producers. It is concluded that it is possible to achieve a balance between economic progress and environmental protection, provided that there is a robust legal framework and cooperation among the various stakeholders involved.